Catalyst- and Solvent-free Three-component Synthesis of Phosphane Sulfides - Alonso, Francisco; Moglie, Yanina (Current Green Chemistry, 2014)
The first three-component synthesis of phosphane sulfides from diphenylphosphane, elemental sulfur, and α,β-unsaturated carbonyl compounds is presented. Reactions proceed under solvent-free conditions in the absence of catalyst, providing the expected β-diphenylphosphorothioyl-functionalised products in moderate-to-high yields. Different experiments revealed that the process takes place through the in situ formation of diphenylphosphane sulfide and subsequent 1,4-addition to the substrate.
Keywords: Alkenes